Influence of surface grinding on corrosion behavior of ferritic stainless steels in boiling magnesium chloride solution. Issue 11 (14th June 2018) - Zhou, Nian; Pettersson, Rachel; Schönning, Mikael; Peng, Ru Lin
Abstract : The influence of grinding operations on surface properties and corrosion behavior of a ferritic stainless steel (FSS), EN 1.4509, has been investigated and limited comparisons also made to the grade EN 1.4622. Surface grinding was performed along the rolling direction of the material. Corrosion tests were conducted in boiling magnesium chloride solution according to ASTM G36; specimens were exposed both without external loading and under four‐point bend loading. The surface topography and cross‐section microstructure before and after exposure were investigated, and residual stresses were measured on selected specimens before and after corrosion tests using X‐ray diffraction. In addition, in situ surface stress measurements were performed to evaluate the actual surface stresses of specimens subject to four‐point bend loading according to ASTM G39. Micro‐pits showing branched morphology initiated from the highly deformed ground surface layer which contained fragmented grains, were observed for all the ground specimens but not those in the as‐delivered condition. Grain boundaries under the surface layer appeared to hinder the corrosion process. No macro‐cracking was found on any specimen after exposure even at high calculated applied loads. Abstract : The influence of grinding operations on surface properties and corrosion behavior of a ferritic stainless steel, EN 1.4509, has been investigated and limited comparisons also made to the grade EN 1.4622. Grain boundaries under the surface layer appeared to hinder the corrosion process. No macro‐cracking was found on any specimen after exposure even at high calculated applied loads.